Designing a Total Site for an entire lifetime under fluctuating utility prices. (2nd January 2015) - Nemet, Andreja; Klemeš, Jiří Jaromír; Kravanja, Zdravko
Abstract: This paper describes a synthesis of Total Site in order to obtain additional energy savings by process-to-process heat integration. Enhanced Heat Integration and economically viable designs can be obtained by establishing an appropriate trade-off between the operating cost and the investment. The aim of this work was to improve the modeling of the Total Site by including proper pressure levels selection for intermediate utilities, preheating of intermediate utilities because of incomplete condensate recovery, pipeline layout design, and optimal pipe design with optimal pressure/temperature drops and optimal insulation thickness and heat losses during transportation along the pipes. Additionally, future utility prices are considered when synthesizing the Total Site as they are expected to influence the trade-off between investment and operating cost. A stochastic multi-period mixed-integer nonlinear programming model for the optimal synthesis of Total Site over its entire lifetime has been developed by including all the above-mentioned design aspects.